Laboratory simulations of wave attenuation by an emergent vegetation of artificial Phragmites australis: an experimental study of an open-channel wave flume - Yiping, Li; Anim, Desmond Ofosu; Wang, Ying; Tang, Chunyang; Du, Wei; Lixiao, Ni; Yu, Zhongbo; Acharya, Kumud; Chen, Li (Journal of Environmental Engineering and Landscape Management, 2015)
This paper presents a well-controlled laboratory experimental study to evaluate wave attenuation by artificial emergent plants (Phragmites australis) under different wave conditions and plant stem densities. Results showed substantial wave damping under investigated regular and irregular wave conditions and also the different rates of wave height and within canopy wave-induced flows as they travelled through the vegetated field under all tested conditions. The wave height decreased by 6%–25% at the insertion of the vegetation field and towards the downstream at a mean of 0.2 cm and 0.32 cm for regular and irregular waves respectively. The significant wave height along the vegetation field ranged from 0.89–1.76 cm and 0.8–1.28 cm with time mean height of 1.38 cm and 1.11 cm respectively for regular and irregular waves. This patterns as affected by plant density and also location from the leading edge of vegetation is investigated in the study. The wave energy attenuated by plant induced friction was predicted in terms of energy dissipation factor (fe) by Nielsen’s (1992) empirical model. Shear stress as a driving force of particle resuspension and the implication of the wave attenuation on near shore protection from erosion and sedimentation was discussed. The results and findings in this study will advance our understanding of wave attenuation by an emergent vegetation of Phragmites australis, in water system engineering like near shore and bank protection and restoration projects and also be employed for management purposes to reduce resuspension and erosion in shallow lakes.First published online: 21 Oct 2015